DESCRIPTION OF TWO NEW SPECIES FROM THE ANTHAXIA WINKLERI SPECIES-GROUP (COLEOPTERA, BUPRESTIDAE) - Baiocchi, Daniele; Magnani, Gianluca (Fragmenta entomologica, 2010)
Anthaxia (Haplanthaxia) kalalae n. sp. and Anthaxia (Haplanthaxia) sagartiana n. sp. from Iran, two new species from the Anthaxia winkleri species-group, are herein proposed and illustrated. The new species are compared with the most similar species, and data about their biology and distribution are given, together with a short account upon the taxonomical position of Anthaxia kalalae.